(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Comedy is a work of fiction characterized by humorous or satirical content that causes laughter. In comedies, Shakespeare gives free rein to his imagination. There are any number of improbable incidents, unexplained accidents, unjustified coincidences. Comedy in general is the genre in which Shakespeare least of all had in mind the reproduction of reality in its authentic form. The degree of their improbability varies. Shakespeare’s work in this genre, The Taming of the Shrew, is implausible from beginning to end. The circumstances offered to the heroes of comedies are the most incredible, but they think and feel like real living people. The most extraordinary circumstances in which the characters of comedies find themselves are such that they face the need to solve issues that have a worldly meaning. In unrealistic conditions, they solve very real life problems that have important moral significance.